Correlation of the adaptability and stability parameters for commercial maize genotypes evaluated in Tocantins, Brazil - Cancellier, Leandro L.; Afférri, Flávio S.; Peluzio, Joenes M.; Dotto, Michel A.; Leão, Fernando F.; Santos, Valdere M. dos (Brazilian Journal of Agricultural Sciences, 2022)
This study aimed to evaluate the adaptability and stability and correlate their parameters to maximize the information about maize genotypes in Tocantins. The experiments were carried out in the cities of Natividade, Formoso do Araguaia, Brejinho of Nazare, Gurupi and Palmas and in two growing seasons, the experimental design was made in randomized blocks with four replications, with 24 genotypes. The productivity was evaluated and the analysis of adaptability and stability, as well as the analysis of correlation between their parameters, were performed. The cultivar XGN5320 stood out with a high average productivity in all locations (6389.8 kg ha-1), and the regression coefficient obtained was 1.16 and not different from a t test, which indicates good adaptation to favorable environments, but does not guarantee a good yield in unfavorable environments. It was concluded that the hybrids XGN5320, XGN6370, DAS2B710, XGN6318 and XGN4210 showed good productivity, adaptability and stability for the evaluated conditions. The adaptability and stability methodology was adequate for the characterization of the genotypes under the conditions studied. It was possible to identify the groups of adaptability, stability and productivity parameters, for the correlation between them.